ANALISIS PERILAKU PEMBELIAN IMPULSIF DALAM KONTEKS LIVE COMMERCE DI PLATFORM SHOPEE - Riduan Siagian; Jumadiah Wardati; Monang Tumangger (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This study examines impulsive buying behavior in the context of live commerce on the Shopee platform, in line with the rapid growth of live commerce in Indonesia. Using a mixed-methods sequential explanatory design, the research integrates a quantitative phase (online survey), a qualitative phase (in-depth interviews and netnography), and stimulus effectiveness testing through A/B testing. The conceptual framework is developed based on the Stimulus–Organism–Response (S-O-R) model with modifications that incorporate social interaction as part of the stimulus and leads to impulsive responses. The findings indicate that live commerce features—such as social interaction features, scarcity cues, entertainment value, and ease of purchase—affect consumers’ psychological states, particularly emotional arousal and FOMO (Fear of Missing Out), which in turn drive impulsive buying. Moreover, social influence and cognitive engagement function as critical moderators that strengthen the relationship between live commerce stimuli and impulsive buying tendencies. Qualitative insights, netnography, transaction data analysis, and eye-tracking results reveal a temporal mechanism of impulsive buying across activation–amplification–action stages, including a predictable “impulse window” within live sessions. The study also highlights post-purchase outcomes, such as regret and the need for self-control, providing both theoretical contributions and practical recommendations for merchants, the platform, and consumers.